Diallel analysis in Indian mustard (Brassica juncea L. Czern & Coss.) - T.M. Shrimali (Electronic Journal of Plant Breeding, 2016)
Diallel analysis excluding reciprocals, comprised of ten parents and their hybrids was carried out to identify high heterotic crosses and their relationship in terms of general and specific combining ability (GCA and SCA) in Indian mustard in year 2013-14. Analysis of variance for GCA and SCA signify differences for all the traits. Ratio of GCA and SCA variances was below unity for all the characters except days to flowering, plant height and harvest index, which suggested superior role of non-additive genetic variance in the inheritance of these traits. Out of 45 specific crosses, the highest economic heterosis was observed in case of five crosses viz., SKM 815 x RGN-303 (30.26 %), GDM 4 x RH-0555 (27.72 %), GDM 4 x RGN-303 (26.67 %), GDM 4 x RGN-282 (25.06 %) and GDM 4 x SKM 518 (18.63 %). The parents GM 3, GDM 4, RH-0555 and RSK-29 were good combiners for seed yield and its component characters. Parents RGN-303 and RSK-29 were good general combiners for oil content. Similarly, GM 3 and RGN-282 for oleic acid.